Bladder endometriosis: a rare entity - Shivani Khandelwal; Atul Khandelwal; Vijayata Sangwan; Parveen Kundu; Sunaina Hooda; Sanjeev Sanjeev (Urogynaecologia International Journal)
The presence of functioning endometrium outside uterine mucosa is called endometriosis. Endometriosis usually involves the pelvic organs, but sometimes extra pelvic organs are also involved, such as the gastrointestinal tract, soft tissues, and urinary tract. The urinary bladder is involved in 84% of cases of urinary tract involvement, in which patients present with hematuria, menouria, and lower abdominal pain. Ultrasound and cystoscopy are important tools for diagnosis. The treatment options are both medical and surgical. Here, we report two rare cases of bladder endometriosis, who presented with atypical symptoms and were managed accordingly. If cured properly and timely, patients can get rid of this annoying disease.